When art makes one: Scripting narratives in the Museum of Islamic art in Cairo - Bruls, Luca (Student Undergraduate Research E-journal!, 2018)
When art makes one by Luca Bruls unfolds an ethnographic case study on narratives exposing the role of nationalism in the exhibition of the Museum of Islamic Art in Cairo, Egypt. Fieldwork among museum staff documents the way they make decisions regarding scenography and organize activities. The research lays bare the motivations of museum staff to use certain techniques and exhibit particular objects. The goal of the research is to find out about ‘how’ and ‘what’ narratives are constructed respectively indicated in the description and presentation of artefacts in the MIA.